The Effect of Reducing Calcium and Phosphorous on Broiler Performance - kheiri, F.; Rahmani, H.R. (International Journal of Poultry Science, 2005)
This study was conducted to evaluate different levels of calcium (Ca) and phosphorous (P) on ileum microbial content, and performance of broilers. In a completely randomized design test with four treatment diets containing; NRC level (control), 10, 20 and 30% lower than NRC level of Ca and P with four replicates and 30 Ross broiler chicken per replicate in 44 days (12-56 days of age), food consumption, feed conversion ratio (FCR), serum and tibia Ca and P, and duodenal and jejunal epithelial protein were evaluated weekly. Results indicated that serum Ca and P was not affected at all, in contrast, Ca and P content of the tibia were significantly (p< 0.05) affected, with the lowest level in 30% reduced group. FCR was also influenced by the levels of Ca and P on the diet significantly (p< 0.05) which reduced by decreasing their levels. Reduction of Ca and P of the ration did not affect the microbial content of the ileum but affected the protein content of the intestinal epithelium significantly (p< 0.05) in different weeks.